Apodemus vs. Eimeria: Evolutionary factors of speciation and genomic diversification in host-parasite system - Mácová, Anna (Jihočeská univerzita, 2021)
This thesis discusses and explains phylogenetic patterns observed in two different organisms: Eimeria, an unicellular parasite, and Apodemus, a rodent that often serves as a host for this parasitic species. The situation in rodents is intuitive, clearly reflecting their biogeographic history. Phylogenetic pattern in A. agrarius corresponds with its spread from the core locality of its distribution eastward. The lack of the genetic variability in European populations hints the recent origin of this population with the low number of founders. The phylogeny of A. flavicollis, a rodent inhabiting almost the whole Europe, reflects the situation during the last glacial maximum (i.e. speciation in several subpopulations that did not interbreed, but retained their independent nature). The situation in Eimeria is more complex. Parasites always fight in "arm races", trying to accommodate to their hosts as best they can, and to avoid their defense. This results in coevolutionary events such as cospeciation, host switches, duplications, and other events that form the genetic variability in parasites. The study of evolutionary relationships in Eimeria may be difficult due to lack or morphological and/or relevant molecular data. This thesis adds more information to this view. Several other studies were also included in this thesis to provide a broader picture of the complexity of host-parasite systems.
Apodemus vs. Eimeria: Evolutionary factors of speciation and genomic diversification in host-parasite system
Keywords: rodents; parasites; coevolution; host-parasite system; coccidia; evolution